DYNAMICS OF VASYL STEFANYK'S CREATIVE THOUGHT: GENERAL REGULARITIES AND PERSONAL EXPERIENCE - Pikhmanets, Roman (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The proposed article is devoted to the understanding of some issues of the psychology of artistic creativity of Vasyl Stefanyk, in particular the category of "artistic and creative process" as its central problem. Thus, the goal is to trace the dynamics of the novelist's creative thought, starting from the emergence of the idea in the spheres of "lower consciousness" and ending with its verbal embodiment. The research methodology is based on the interdisciplinary nature of the problem under discussion and involves inductive-empirical, objective-analytical and psychological studies. The principles of philological, psychobiographical and comparative-historical research methods, as well as the achievements of the latest methodology: phenomenology, literary hermeneutics and receptive aesthetics are applied. As a result of scientific research, the peculiarities of combining in Vasyl Stefanyk’s creative experience the general regularities of the procedural structure of creativity with individual and unique manifestations have been clarified. Emphasis is placed on such aspects as the psychological mechanisms of the emergence of artistic design, its appearance in consciousness in the form of a prototype, crystallization in concrete-sensory forms and verbal realization. The scientific novelty of the article is that it highlights the subjective and psychological factors of conditionality of artistic phenomena, which helps to learn them more deeply and fully.